STORA JONSHOLMEN - AN ISLAND WITHIN OUR REACH - Wimnell, Viggo (My University, 2020)
This thesis deals with the citizens of Gothenburg’s access to the sea and coastlines and is all about making the unreachable available and open for the public. It can be seen as a response to the shoreline protection law in Sweden that in practice not always functioning as it was intended and our unequal possibilities regarding this. The municipality owned island of Stora Jonsholmen in the western part of the city truly enables unique possibilities. It is close to the city center both in terms of geographical position and public transport systems but first of all close enough to unite to the mainland with a bridge. Through an architectural investigation and a number of wood structures this thesis strives to transform Stora Jonsholmen to a seabathing and excursion point easy accessible and welcoming to all. In particular those who otherwise do not reach archipelago settings like this. The design approach is focusing on simple and rational wood based constructions with standardized materials and well proven methods. The ambition is to combine them into a well thought whole that becomes more than each object itself. The design proposal includes a pedestrian bridge, changing - and restaurant pavilion, all which are built in wood and reachable through a wheelchair accessible walkway loop.
Keywords: public, sea bath, timber, wood, pedestrian bridge, walkway, archipelago